Epigenetic changes in healthy human skeletal muscle following exercise– a systematic review. Issue 7 (3rd July 2019) - Jacques, Macsue; Hiam, Danielle; Craig, Jeffrey; Barrès, Romain; Eynon, Nir; Voisin, Sarah
ABSTRACT: Exercise training is continually challenging whole-body homeostasis, leading to improvements in performance and health. Adaptations to exercise training are complex and are influenced by both environmental and genetic factors. Epigenetic factors regulate gene expression in a tissue-specific manner and constitute a link between the genotype and the environment. Moreover, epigenetic factors are emerging as potential biomarkers that could predict the response to exercise training. This systematic review aimed to identify epigenetic changes that have been reported in skeletal muscle following exercise training in healthy populations. A literature search of five databases (PUBMED, MEDLINE, CINHAL, SCOPUS and SportDiscuss) was conducted in November 2018. Articles were included if they examined epigenetic modifications (DNA methylation, histone modifications and non-coding RNAs) in skeletal muscle, following either an acute bout of exercise, an exercise intervention in a pre/post design, or a case/control type of study. Twenty-two studies met the inclusion criteria. Several epigenetic markers including DNA methylation of genes known to be differentially expressed after exercise and myomiRs were reported to be modified after exercise. Several epigenetic marks were identified to be altered in response to exercise, with potential influence on skeletal muscle metabolism. However, whether these epigenetic marks play a role in the physiological impact of exercise is unclear. Exercise epigenetics is still a very young research field, and it is expected that in the future the causality of such changes will be elucidated via the utilization of emerging experimental models able to target the epigenome.